Mechanical support of hemodynamics by IABK early period after heart valve replacement - A. A. Beregovoj; E. V. Aksenov; E. O. Lebedeva; A. K. Logutov; R. B. Demchenko (Ukrainian Journal of Cardiovascular Surgery, 2016)
In this work the group who were implanted intra-aortik balloon kontrpulsator in connection with refractory left ventricular failure. The purpose of the IABK- must balance myocardial oxygen consumption with its delivery. In most cases such therapeutic measures as a destination inotropes, vasodilators, diuretics, solutions for volume replacement is enough to bring patsient a critical state, sometimes these events is not enough, then in this cases recommended VCB. Traumatic cardiac surgery, with increased metabolic needs during operations on the valves can cause heart, in turn, is unable to provide systemic hemodynamics.